Multidimensional scaling of D15 caps: color-vision defects among tobacco smokers? - Bimler D; Kirkland J (CAMBRIDGE UNIV PRESS, 2004)
Tobacco smoke contains a range of toxins including carbon monoxide and cyanide. With specialized cells and high metabolic demands, the optic nerve and retina are vulnerable to toxic exposure. We examined the possible effects of smoking on color vision: specifically, whether smokers perceive a different pattern of suprathreshold color dissimilarities from nonsmokers. It is already known that smokers differ in threshold color discrimination, with elevated scores on the Roth 28-Hue Desaturated panel test. Groups of smokers and nonsmokers, matched for sex and age, followed a triadic procedure to compare dissimilarities among 32 pigmented stimuli (the caps of the saturated and desaturated versions of the D15 panel test). Multidimensional scaling was applied to quantify individual variations in the salience of the axes of color space. Despite the briefness, simplicity, and "low-tech" nature of the procedure, subtle but statistically significant differences did emerge: on average the smoking group were significantly less sensitive to red-green differences. This is consistent with some form of injury to the optic nerve.
Keywords: Multidimensional scaling; Colour vision deficiency; D15 panel test; Smoking; Fields of Research::380000 Behavioural and Cognitive Sciences